IMPROVING PPKn LEARNING MOTIVATION THROUGH COOPERATIVE LEARNING TYPE INDEX CARD MATCH STUDENTS CLASS VI - Asmanidar Asmanidar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by the low motivation to learn class VI students of SD Negeri 021 Tarai Bangun Kampar Regency. This study aims to increase the learning motivation of Civics in Class VI students of SD Negeri 021 Tarai Bangun, Kampar Regency using Cooperative Learning Type Index Card Match. The subjects of this study were all Class VI students of SD Negeri 021 Tarai Bangun Kampar Regency, totalling 32 people. The form of research is classroom action research. The research instrument used was a performance instrument and an observation sheet of teacher activity and student activity. The results showed, in Cycle I the research score reached a score of 132 high criteria, with an average student motivation for each learning motivation indicator of only 68.8%. While the observations of learning motivation in cycle II reached a score of 163 very high criteria, the average student motivation for learning motivation indicators was 84.9%. thus it can be concluded that through cooperative learning index card match type can increase students' PKn learning motivation